Safer Electrolytes for Lithium‐Ion Batteries: State of the Art and Perspectives. Issue 13 (15th June 2015) - Kalhoff, Julian; Eshetu, Gebrekidan Gebresilassie; Bresser, Dominic; Passerini, Stefano
Abstract Lithium‐ion batteries are becoming increasingly important for electrifying the modern transportation system and, thus, hold the promise to enable sustainable mobility in the future. However, their large‐scale application is hindered by severe safety concerns when the cells are exposed to mechanical, thermal, or electrical abuse conditions. These safety issues are intrinsically related to their superior energy density, combined with the (present) utilization of highly volatile and flammable organic‐solvent‐based electrolytes. Herein, state‐of‐the‐art electrolyte systems and potential alternatives are briefly surveyed, with a particular focus on their (inherent) safety characteristics. The challenges, which so far prevent the widespread replacement of organic carbonate‐based electrolytes with LiPF6 as the conducting salt, are also reviewed herein. Starting from rather "facile" electrolyte modifications by (partially) replacing the organic solvent or lithium salt and/or the addition of functional electrolyte additives, conceptually new electrolyte systems, including ionic liquids, solvent‐free, and/or gelled polymer‐based electrolytes, as well as solid‐state electrolytes, are also considered. Indeed, the opportunities for designing new electrolytes appear to be almost infinite, which certainly complicates strict classification of such systems and a fundamental understanding of their properties. Nevertheless, these innumerable opportunities also provide a great chance of developing highly functionalized, new electrolyte systems, which may overcome the afore‐mentioned safety concerns, while also offering enhanced mechanical, thermal, physicochemical, and electrochemical performance.